Comparing Health Promotion Programs in Public Dental Service of Vantaa, Finland: A Clinical Trial in 6–36-Month-Old Children - Irma Arpalahti; Mimmi Tolvanen; Kaisu Pienihakkinen (International Journal of Dentistry)
Objective. The study assessed whether the new family-based programs in health promotion or the training of dental professionals had an impact on the colonization of mutans streptococci (MS) in young children. Material and Methods. The participants were children born in 2008 and inhabitants of Vantaa aged 24–36 months. The families with first-born children were invited to a questionnaire study. Vantaa was categorized into three matching areas, which were randomly assigned to different programs. New counseling methods were trained. The routine program used earlier served as the control group. The children born in 2006 served as a historic control. The outcome measure was the presence of MS. Statistical method was logistic regression. Results. Colonization of MS was found only in few children born in 2006 or 2008; 15% and 11%, respectively. Within the 2008 birth cohort, the addition of parental counseling did not improve the routine program. Instead, the father’s advanced level of education () and the child’s reported the use of xylitol at least three times a day () associated with negative MS scores. Conclusions. The routine program and training of the professionals seem to reduce the proportion of children with MS more than adding parental self-care to oral health programs.